2022
DOI: 10.1111/sifp.12190
|View full text |Cite
|
Sign up to set email alerts
|

A “Plus” Model for Safe Transitions to Adulthood: Impacts of an Integrated Intervention Layered onto A National Social Protection Program on Sexual Behavior and Health Seeking among Tanzania's Youth

Abstract: Poverty is a structural driver of risky sexual behaviors. While cash transfers can mitigate some of this risk, complementary interventions have been posited as a way to further reduce multidimensional vulnerability. We examine the impacts of a multicomponent intervention targeted to Tanzanian adolescents on their sexual behaviors and reproductive health. The intervention comprised livelihood and life skills training, mentoring, and health facilities’ strengthening. Data come from a cluster randomized controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…This may be due to a number of reasons. While this intervention has been previously demonstrated to be protective along several pathway indicators, including gender-equitable attitudes [49], increased knowledge related to contraception and HIV prevention [50], mental health [51] and economic activities [47], it was perhaps not sufficient to overcome all the interrelated social, relational and economic vulnerabilities which lead AGYW to engage in transactional sex. Alternatively, the lack of impacts may be reflective of alternative drivers of engagement in transactional sex, namely choice of partners, addressing low self-esteem or a need to boost one's own power and social status [6,52].…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to a number of reasons. While this intervention has been previously demonstrated to be protective along several pathway indicators, including gender-equitable attitudes [49], increased knowledge related to contraception and HIV prevention [50], mental health [51] and economic activities [47], it was perhaps not sufficient to overcome all the interrelated social, relational and economic vulnerabilities which lead AGYW to engage in transactional sex. Alternatively, the lack of impacts may be reflective of alternative drivers of engagement in transactional sex, namely choice of partners, addressing low self-esteem or a need to boost one's own power and social status [6,52].…”
Section: Discussionmentioning
confidence: 99%
“…The two Kenyan studies conducted both in slum (42) and pastoral (46) settings reported that effect of these multiple component interventions comprising violence prevention, education and health was not significantly different from that of standalone (violence prevention) intervention. Similarly, a Tanzanian study reported there was no significant difference in the rates of teen pregnancy among girls in an arm with multicomponent interventions compared to those girls in the "cash only" arm (arm that received the cash transfer program alone) (48). The multicomponent interventions comprised cash transfer conditioned up on school enrolment or seeking essential health services and unconditional cash transfer plus livelihoods and life skills training, mentoring and an asset transfer, combined with linkages to strengthened government-run HIV and SRH services).…”
Section: Effectiveness Of the Intervention On Teen Pregnancymentioning
confidence: 98%
“…Among the included studies that reported on child marriage, four of them reported on the effect of three component interventions. These projects were conducted in Ethiopia (44), Kenya (46), Tanzania (48). One study was a multicounty study conducted in Tanzania and Burkina Faso (43).…”
Section: B Programs/projects That Addressed Three Componentsmentioning
confidence: 99%
See 2 more Smart Citations